2021
DOI: 10.4274/ejbh.galenos.2021.2021-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Oncoplastic Breast-Conserving Surgery According to Tumor Location

Abstract: The use of oncoplastic breast surgery is an essential cornerstone for breast cancer management. The main aim of breast cancer surgery is to obtain an adequate oncological safety margin. Still, the cosmetic outcome also seems important for social and psychological wellbeing and quality of life. After breastconserving surgery, the remaining breast may be reconstructed with volume displacement or volume replacement techniques. A better cosmetic outcome can be achieved by selecting appropriate surgical techniques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 32 publications
0
16
0
2
Order By: Relevance
“…Considering the evidence in the literature, oncoplastic surgery was found to have low recurrences while improving the cosmetic outcome and patients' quality of life [10,[57][58][59][60][61][62][63][64][65][66][67].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the evidence in the literature, oncoplastic surgery was found to have low recurrences while improving the cosmetic outcome and patients' quality of life [10,[57][58][59][60][61][62][63][64][65][66][67].…”
Section: Resultsmentioning
confidence: 99%
“…These techniques have demonstrated promising results as a safer tool to handle large, complex tumors and lesions in difficult anatomical locations, whether multifocal or progressing on neoadjuvant therapy. As expected, the application of oncoplastic techniques has witnessed the emergence of new problems with margin adequacy due to the unavoidable displacement or replacement of residual breast tissue surrounding the excised tumor, according to excision size and location [58][59][60]. Regardless, the current literature demonstrates that oncoplas-tic surgery is a safe option in terms of re-excision, completion mastectomy rates, and local and distant recurrence [10,[61][62][63][64][65][66]; such surgery is oncologically safe and has been recommended in the case of DCIS [67].…”
Section: Evolution Of Margin Acceptabilitymentioning
confidence: 90%
“…Additionally, in accordance with the results, we found that patients with tumors in the outer quadrant had a significantly better prognosis than those with tumors in the inner quadrant or center location. This may be because the outer quadrant is a favorable location for large-volume excision to gain adequate surgical margins, especially for small tumors ( 34 ). Therefore, the low-risk group was safe enough and may gain limited benefit from RT.…”
Section: Discussionmentioning
confidence: 99%
“…Glandular density, patient-related risk factors (smoking, obesity, diabetes, previous surgery, etc. ), adjuvant treatments, patient preferences and expectations are other specific factors that will influence decision making with regards to the OBS technique [7,8].…”
Section: Review Oncoplastic Approaches To Breast Conservationmentioning
confidence: 99%
“…The objective is tumor excision without skin resection, and to repair partial breast defects effectively to reduce the risk of deformity that will occur with the effect of RT. The main principles are the localization of the tumor, planning the incision, dissecting the subcutaneous flap widely beyond the tumor, identifying the tumor, removing the specimen, undermining the breast anterior to the pectoralis fascia, marking the tumor cavity, and closure of the defect with mobilized tissue pillars [8].…”
Section: Review Oncoplastic Approaches To Breast Conservationmentioning
confidence: 99%